Joubert Syndrome, A Ciliopathy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2013)
Investigators at Neurogenetics Unit, Mendel Laboratory, Rome, and University of Salerno, Italy, review the clinical features and genetic basis of Joubert syndrome, overlap with other ciliopathies, and the multifaceted roles of primary cilia in CNS development.